Control De Inventario En El Local Comercial Jenny Beauty De La Ciudad De Babahoyo - Larenas Sojos, Derian David (2019)
Every business that is dedicated to the purchase or sale of goods or services has to keep an adequate control of its inventory since this will allow you to know which is the one that rotates more or which rotates less, a bad control of Inventories can bring some problems for the company in its sales and at the time of its accounting entries. Inventory management is an important part of any business. (Boubeta M. M., 2006) defines inventory as "inventory is a stored resource that is used to satisfy a current or future need" (page 1). That is why this case study is based on inventory control at the Jenny Beauty store in the city of Babahoyo, which is framed within the accounting information management research subline since inventory is a fundamental part of the accounting information for decision making.